Motivated Belief Updating and Rationalization of Information - Christoph Drobner; Sebastian J. Goerg (Institute of Labor Economics (IZA), 2022)
We study belief updating about relative performance in an ego-relevant task. Manipulating the perceived ego-relevance of the task, we show that subjects update their beliefs optimistically because they derive direct utility flows from holding positive beliefs. This finding provides a behavioral explanation why and how overconfidence can evolve in the presence of objective information. Moreover, we document that subjects, who received more bad signals, downplay the ego-relevance of the task. Taken together, these findings suggest that subjects use two alternative strategies to protect their ego when presented with objective information.
Keywords: C91; D83; D84; 330; motivated beliefs; optimistic belief updating; overconfidence; direct belief utility; Bayes' rule; ex-post rationalization